2003
DOI: 10.1046/j.1432-1033.2003.03926.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization, purification and properties of a tetrathionate hydrolase from Acidithiobacillus caldus

Abstract: The moderately thermophilic bacterium Acidithiobacillus caldus is found in bacterial populations in many bioleaching operations throughout the world. This bacterium oxidizes elemental sulfur and other reduced inorganic sulfur compounds as the sole source of energy. The purpose of this study was to purify and characterize the tetrathionate hydrolase of A. caldus. The enzyme was purified 16.7-fold by one step chromatography using a SP Sepharose column. The purified enzyme resolved into a single band in 10% polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 36 publications
3
66
0
Order By: Relevance
“…This might be the reason why we failed to detect the TetH activities of strains grown on sulfur. A similar negative result was also reported for Acidithiobacillus caldus, in which TetH activity was not detected in the crude enzyme extract when the organism was cultivated in liquid medium with elemental sulfur as the energy source (10). As TetH is thought to be responsible for the hydrolysis of tetrathionate to thiosulfate, sulfur, and sulfate, the upregulation of doxD2 in the tetH overexpression strain and its downregulation in the ⌬tetH mutant according to qRT-PCR analysis indicated that the predicted doxD2 operon (5, 36) might play an important role in thiosulfate metabolism in A. ferrooxidans.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This might be the reason why we failed to detect the TetH activities of strains grown on sulfur. A similar negative result was also reported for Acidithiobacillus caldus, in which TetH activity was not detected in the crude enzyme extract when the organism was cultivated in liquid medium with elemental sulfur as the energy source (10). As TetH is thought to be responsible for the hydrolysis of tetrathionate to thiosulfate, sulfur, and sulfate, the upregulation of doxD2 in the tetH overexpression strain and its downregulation in the ⌬tetH mutant according to qRT-PCR analysis indicated that the predicted doxD2 operon (5, 36) might play an important role in thiosulfate metabolism in A. ferrooxidans.…”
Section: Discussionsupporting
confidence: 80%
“…Tetrathionate can be hydrolyzed to thiosulfate, sulfate, and sulfur by tetrathionate hydrolase (TetH) (7)(8)(9). Compared with TetH from the sulfur-oxidizing strain Acidithiobacillus caldus (10,11), TetH from A. ferrooxidans was speculated to be phylogenetically distinct (11,12) and even diverse in its catalytic reaction on account of different cofactor requirements (10,13). In addition, the subcellular location of TetH in A. ferrooxidans has not been certain until now because it has been reported as a periplasmic (8), outer membrane-associated (12,14), and extracellular (15) protein.…”
mentioning
confidence: 99%
“…thiooxidans, and At. caldus), [20][21][22][23] in Acidiphilium acidophilum, 24) and in the thermoacidophilic archaeon Ad. ambivalens.…”
Section: )mentioning
confidence: 99%
“…caldus and Ad. ambivalens, 22,25) Af-Tth is synthesized in both tetrathionateand sulfur-grown cells.…”
Section: )mentioning
confidence: 99%
“…Some chemotrophs additionally utilize tetrathionate (S 4 O 6 2Ϫ ) and other polythionates as energy and electron sources. Tetrathionate is also produced as an intermediate during the oxidation of thiosulfate by several beta-and gammaproteobacteria which follow the so-called tetrathionate intermediate (S 4 I) pathway (2)(3)(4)(5). Although a few alphaproteobacteria can oxidize tetrathionate as a starting substrate, none of them form tetrathionate during thiosulfate oxidation (6)(7)(8).…”
mentioning
confidence: 99%